IRRIGANTS AND DIFFERENT IRRIGATION SYSTEMS IN ENDODONTICS - RETROSPECTIVE LITERATURE - Corina Armulescu; Ionela Teodora Dascălu; Marilena Bătăiosu; Luminița Dăguci; Adrian Camen; Oana Andreea Diaconu; Ruxandra Voinea Georgescu; Adina Turcu; Mihaela Jana Țuculină (Romanian Society of Oral Rehabilitation, 2021)
This study is a literature review in order to irrigants in endodontics. A successful endodontic treatment relies on eradicating the germs found in the canal system and preventing reinfection. Alongside the irrigants commonly used in endodontics, in order for the treatment to be successful there have been introduced different irrigation systems that bring benefits such as: decreased time to act and the way of penetration at the isthmi level and lateral canals and of irrigation substances, where instrumentation is not sufficient.